Assessment of Al3+ Ion Selectivity Coefficient (Kij) in Polyurethane Membranes Derived from Castor Oil (Ricinus communis. L) via Separated Solution Method - Jannah, Firaihanil; Idroes, Rinaldi; Nazaruddin, Nazaruddin; Idris, Nasrullah; Safitri, Eka; Md Sani, Nor Diyana (Graha Primera Saintifika, 2023)
The influence of foreign ions on the response of Al3+ ISE-based polyurethane membranes from castor oil has been determined using SSM. The results showed that the presence of the foreign ions tested did not affect the sensitivity and response of Al3+ ISE. The influence of foreign ions Na+, K+, Li+, Pb2+, Ca2+, Co2+, Cu2+, Ni2+, Cr3+, and Fe3+ on the selectivity of ion-selective electrodes (Al3+ ISE) in the concentration range 1x10-9 – 1x10-4 M has been performed using separate methods. The results show that the presence of foreign ions does not affect the performance of Al3+ ISE with a Kij value < 1. The selectivity sequence of foreign ions is Fe3+ > Cr3+ > Pb2+ > Cu2+ > Ni2+ > Co2+ > Ca2+ > Li+ > Na+ > K+ respectively.